Accounting information system performance in hospital: A case study - Muhamad Rifandi; Rofiqah Niyati Rahayu (Journal of Contemporary Accounting, 2023)
This study aims to examine the impact of user engagement in system development, training and education, top management support, and user capabilities on the performance of accounting information systems. The population of this study consisted of 13 employees from the finance department of the PKU Muhammadiyah Gamping Yogyakarta Hospital who used an accounting information system. This was a mixed methods study, which combined quantitative and qualitative data in one study. Data collection methods included questionnaires and interviews. The SPSS version 22 program was used for data analysis, which included descriptive analysis and multiple regression analysis. The results of the study are that user engagement in system development, user education and training programs, and top management support all have an impact on the performance of accounting information systems. Meanwhile, user capabilities have no effect on accounting information system performance. It can also be expanded by including independent variables and research objects.